Tumefacção parotidea: Primeira manifestação de linfoma de Hodgkin - Caravaca-García, Antonio; Franco, Rafael; Guerrero-Cauqui, Rosario; Ruiz-Fito, Rafael (Revista Portuguesa de Otorrinolaringologia-Cirurgia de Cabeça e Pescoço, 2011)
The finding of lymphomas in the salivary glands is uncommon. Moreover, the diagnosis of Hodgkin´s lymphoma from the finding of an initial swelling that is increasingly growing in the parotid region is rare. The clinical examination, the FNA or the radiology investigations including CT scan, will hardly help in understanding the nature of the disease. Because of this, lymphoma must be taken into account in the differential diagnosis of parotid masses.